Patient profile and reasons for the absence from scheduled medical appointments - Baptista, Simone Cristina Paixão Dias [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Corrente, José Eduardo [UNESP]; Trettene, Armando Dos Santos; Lima, Silvana Andrea Molina [UNESP]; Spiri, Wilza Carla [UNESP] (Universidade Estadual de Maringa, 2024)
Organizing health services is a challenge for managers. Moreover, patients’ absenteeism to appointments is a relevant issue. This study aims to evaluate the profile of absent users, the medical specialty, and reasons for absence from medical consultations in a reference clinic. This is a cross-sectional study conducted at a tertiary hospital in the state of São Paulo. Data was obtained from reports from the Hospital Center for Medical Informatics and electronic patient records (from January 1st to December 31st, 2018). Structured interviews were carried out (from April 2018 to February 2019) by phone with a random sample of 317 patients who were aged 18 years old or above and missed consultations in twelve medical specialties, after approval by the Research Ethics Committee. Analysis were performed using descriptive and analytical statistics, with a significance level set at 5%. In total, 69.09% of patients say they missed consultations. It is noteworthy that 18.06% of patients said they attended consultations, followed by those who claimed to be sick or hospitalized (16.98%, p-value=0.0006). Analyzing the context and reasons for absences generates knowledge for service management. We found inadequacies in scheduling and system records. Patients and health services must be co-responsible for optimizing the use of public health resources.
Keywords: Absenteeism; ambulatory assistance; non-attending patients; nursing administration research